Preparation of continuous carbon fiber reinforced PA6 prepreg filaments with high fiber volume fraction - Ming Zhang; Zhonggang Sun; Yingbing Liang; Yanhua Guo; Guoqing Dai; Keyuan Wei; Ming Li; Xiping Li; Igor V. Alexandrov (Additive Manufacturing Letters)
High-performance continuous carbon fiber prepreg filaments have been a research hotspot in the field of additive manufacturing in recent years, and are considered to be an effective option for improving the mechanical strength of thermoplastic composite parts. However, the effect of fiber volume fraction on the microstructure and tensile properties of 3D printed prepreg filaments remains miss. Therefore, this study selected suitable impregnation processes and materials to prepare prepreg filaments with different fiber volume fraction and investigated their mechanical properties and microscopic morphologies. The results show that the increase of fiber volume fraction effectively promoted the interface bonding between fiber and resin, and increased capacity for load transfer. When the fiber volume fraction was 54.0 %, the tensile strength of the prepreg filaments and specimens reached 1977 MPa and 334 MPa, respectively. This study can provide a process optimization strategy for the preparation of more types of continuous fiber prepreg filaments with high fiber volume fraction, as well as a data reference for the preparation of high-performance 3D-printed thermoplastic composites.